2020
DOI: 10.3389/fbioe.2020.00869
|View full text |Cite
|
Sign up to set email alerts
|

Micro Versus Macro – The Effect of Environmental Confinement on Cellular Nanoparticle Uptake

Abstract: While the microenvironment is known to alter the cellular behavior in terms of metabolism, growth and the degree of endoplasmic reticulum stress, its influence on the nanoparticle uptake is not yet investigated. Specifically, it is not clear if the cells cultured in a microenvironment ingest different amounts of nanoparticles than cells cultured in a macroenvironment (for example a petri dish). To answer this question, here we used J774 murine macrophages and fluorescent nanodiamonds (FND) as a model system to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Nanodiamonds have excellent biocompatibility in many different cell lines (in vitro) like HT-29 [ 5 ], macrophages, yeast cells [ 6 ], BHK-21 [ 7 ], MCF-7 [ 8 ]. Prabhakar et al showed no toxicity after incubating MDA-MB-231 (human breast adenocarcinoma) cells with FNDs for 120 h. While other carbon nanomaterials have been reported to cause proinflammatory responses [ 9 ] this is not the case for nanodiamonds [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanodiamonds have excellent biocompatibility in many different cell lines (in vitro) like HT-29 [ 5 ], macrophages, yeast cells [ 6 ], BHK-21 [ 7 ], MCF-7 [ 8 ]. Prabhakar et al showed no toxicity after incubating MDA-MB-231 (human breast adenocarcinoma) cells with FNDs for 120 h. While other carbon nanomaterials have been reported to cause proinflammatory responses [ 9 ] this is not the case for nanodiamonds [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…(b) Overview of FNDs destination throughout cellular processes, such as cell−cell communication (14), proliferation (15), migration (16), and trafficking inside cells (17). Representative literature can be found for each image: (1), 11,142,143 (2) and (3), 144 (4), 90 (5), 142,147,148 (6) and ( 7), 150 (8), 47,157 (9), 155,157 (10), 155 (11), 158 (12), 168,173 (13), 161 (14), 168 (15), 179 (16), 141 Better understanding of FNDs trafficking via endosomes requires co-localization with other biomarkers which still seems to be a challenge on the labeling and image processing levels. Another challenge is to understand what the recorded trajectories mean.…”
Section: ■ Labelingmentioning
confidence: 99%
“…(b) Overview of FNDs destination throughout cellular processes, such as cell−cell communication (14), proliferation (15), migration (16), and trafficking inside cells (17). Representative literature can be found for each image: (1), 11,142,143 (2) and (3), 144 (4), 90 (5), 142,147,148 (6) and ( 7), 150 (8), 47,157 (9), 155,157 (10), 155 (11), 158 (12), 168,173 (13), 161 (14), 168 (15), 179 nanoparticles that contain high concentrations of SiV centers. While this might be beneficial for some of the quantum sensing applications presented in NV Center-Based Sensing and Magnetometry, this is not desirable in labeling applications where high brightness is needed.…”
Section: ■ Labelingmentioning
confidence: 99%
See 2 more Smart Citations